Organizational and legal regulation procedure for circulation of extemporal medicines based on pharmaceutical law - Shapovalov, V.Jr. V.; Zbrozhek, S; Shapovalova, V; Shapovalov, V V (Annals of Mechnikov’s Institute, 2019)
Introduction.The paper studied the situation regarding the production of medicines in pharmacies. Established that the presence of the pharmacy manufacture of medicines, patients entitled to receive medicines made to the needs of individuals. Goal –to study the organizational and legal procedure of regulation of extemporal medicines by developing of the algorithm for determining the legal act used in the event of conflict based on the law pharmaceutical law. Materialsandmethods. The materials of the study were legal acts of Ukraine: Laws of Ukraine, Decrees of the Cabinet of Ministers of Ukraine, Orders of the Ministry of Healthcare of Ukraine. The research methods were legal, documentary and comparative analyzes.Results and discussion. However, production of extemporaneous preparations in the pharmacy requires a production base and the appropriate staff. Therefore, the authors based on pharmaceutical law proposed organizational and legal procedure regarding the regulation of extemporaneous preparations by developing the algorithm for determining the legal act which should follow in the event of conflicts concerning the law. Conclusions. Based on pharmaceutical law held organizational and legal procedure for the regulation of circulation of extemporal medicines. Proposed the algorithm for determining of the legal act used in the practice of pharmacy professionals. Considered the professional status of an authorized person on the stage of quality control of extemporal medicines in their treatment in healthcare institutions of private property.